Contribution of Teacher Professionalism in the World of Education - M Zainul Hafizi (International Journal of Applied Educational Research (IJAER), 2024)
This study aims to investigate the contribution of teacher professionalism in education, with a focus on the impact of teacher quality on student learning outcomes, relevant and tailored learning strategies, and the role of teachers in shaping student character. The research method used a qualitative approach with literature analysis. The results indicate that teacher quality has a significant influence on students' academic achievement, while a responsive approach to individual student needs and the cultivation of student character also play an important role in the development of a sustainable society.